The mixed martial arts athlete: A physiological profile - Lenetsky, S.; Harris, N. (Strength and Conditioning Journal, 2012)
Mixed martial arts (MMA) is a combat sport that has gained much popularity in recent years. Despite this recent surge in popularity, there is little research on the physiological demands of the sport. Consequently, strength and conditioning practices are still based largely on anecdotal evidence and tradition. This review examines the research on MMA and the associated component sports in an attempt to underpin future training practices with an evidence base.